Effects of home-based slow-paced breathing on functional performance in middle-aged women: A randomized controlled trial study - Karama Masmoudi; Fatma Chaari; Haithem Rebai; Sonia Sahli (Experimental Gerontology, 2025)
As individuals age, functional performance declines, particularly affecting mobility, strength, and postural balance, with middle-aged women experiencing earlier and more pronounced impairments due to menopausal transition. Given the low adherence to traditional exercise programs among this population, home-based slow-paced breathing (SPB) presents a promising accessible alternative. Hence, this study aimed to examine the effects of a 12-week daily SPB intervention on functional performance in middle-aged women.Twenty-six middle-aged women were randomized into an experimental group (EG), which practiced home-based SPB, or a control group (CG), which continued their usual activities. Static postural balance, upper- and lower-limb muscle strength, mobility and dynamic balance, and aerobic endurance were evaluated at pre-intervention, post-4, post-8, and post-12 weeks of intervention.Static postural balance improved on a firm surface within the EG post-12 weeks of intervention, though no significant differences emerged between groups. On a foam surface, improvements emerged post-8 weeks in the eyes-open condition and post-4 weeks in the eyes-closed condition. Additionally, aerobic endurance improved within the EG post-8 weeks, with no significant differences between groups. No significant group x session interactions were found for other functional performances.These findings indicate that middle-aged women who practiced or not the SPB demonstrated similar functional outcomes, suggesting that SPB alone may not be sufficient to induce significant improvements in functional performances. Exploring the effects of integrating SPB with muscle-strengthening exercises or neuromuscular training could be interesting to determine whether a combined approach could yield greater functional benefits and address the limitations of the observed non-significant results.